Interpretasi Makna Individual Spiritual Pada Ziarah Wali Sultan Maulana Hasanuddin Banten - Sudarmika, Dina; Helmina, Sachri Suci (FISIP Universitas Bung Karno, 2025)
This study explores the spiritual, social, and moral significance of pilgrimages to the tombs of Islamic saints within the broader landscape of religious tradition. Employing a qualitative phenomenological approach, the research uncovers that pilgrimages are not merely ritual acts but serve as deeply personal journeys akin to Hajj, Hijrah, and Rihlah. The findings reveal that pilgrimage fosters an elevation of religious consciousness, strengthens faith, and provides spiritual equilibrium amid the complexities of life. Furthermore, the act of ziarah facilitates silaturrahmi—a spiritual networking process that reinforces communal ties and moral values. Through the interaction between the pilgrim and the Divine, pilgrimage emerges as a vital practice that enriches both individual spirituality and collective ethical culture.Keyword: Meaning, Spiritual Value, Pilgrim